Cal Poly S.L.O. African American Student Union [banner held by Black student] (1993)
The student is wearing a shirt with an illustration of Martin Luther King Jr., a California Angels jacket, and a hat (possibly with an 'X' for Malcolm X). The student is standing on the Dexter Lawn sidewalk in front of the Engineering West building.